ChemInform Abstract: Catalytic Synthesis of 3‐Thioindoles Using Bunte Salts as Sulfur Sources under Metal‐Free Conditions. Issue 40 (September 2016) - Qi, Hong; Zhang, Tongxin; Wan, Kefeng; Luo, Meiming
Abstract: The title protocol is advantageous with respect to the use of odorless and stable Bunte salts as sulfenylating agents and iodine as non metallic catalyst.